(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Eclipta alba has been used in Ayurvedic medicine for treatment of various ailments. An attempt has been made to optimize different extraction conditions for Eclipta alba. Further an accurate, precise, reproducible and sensitive accurate, precise and reproducible (HPTLC) method has been developed for the estimation of Wedelolactone in Eclipta alba. An attempt has been made to quantify wedelolactone in various extracts by HPTLC method. Precoated aluminum silica gel F plates were used as stationary phase and toluene: ethyl acetate (9:1) was used as mobile phase. This system was found to give compact spots for wedelolactone (RF value of 0.30 ± 0. 3) with a linearity range of 1 to 80 µg per spot. The proposed method was applied to evaluate efficiency of different methods of extraction i.e. percolation, maceration, hot solvent extraction (Soxhlet apparatus), supercritical fluid extraction, microwave, orbital shaker bath and sonication method for extraction of wedelolactone from Eclipta alba.